To use or be used? The role of agency in social media use and well-being - Lee, Angela Y.; Ellison, Nicole B.; Hancock, Jeffrey T. (Frontiers in Computer Science, 2023)
In this paper, we develop the concept of agentic social media use: a way of engaging with social media that emphasizes having the beliefs, knowledge, and practices to use it intentionally. In comparison to instances of “mindless” social media use, people who use social media agentically do so with a purpose in mind: they leverage the affordances of social media to do things that are meaningful, useful, or satisfying for them. For example, people can use social media to intentionally build or manage their relationships, to seek out and learn new information about their interests, or to craft a positive image of themselves through the content they post. Crucially, however, there are many other valuable uses of social media that may not be considered conventionally “productive” but are nonetheless deliberate and useful, such as using social media intentionally to relax, unwind, and entertain themselves (e.g., to modulate their emotions, Knobucher-Westerwick, 2015; Robinson & Knobucher-Westerwick, 2016). To use social media agentically means to (1) hold an agentic mindset about one’s relationship with social media, (2) have the knowledge and literacy to understand how to navigate social media effectively, and (3) enact practices that assert control over specific elements of social media use, such as curating content and refining algorithmic recommendation. Approaching social media use from the perspective of agency and intentionality allows us to better understand heterogeneous social media effects and to identify new ways of helping people benefits from these technologies.